Synthesis and coherent properties of 13C-enriched sub-micron diamond particles with nitrogen vacancy color centers. (15th September 2020) - Mindarava, Yuliya; Blinder, Rémi; Liu, Yan; Scheuer, Jochen; Lang, Johannes; Agafonov, Viatcheslav; Davydov, Valery A.; Laube, Christian; Knolle, Wolfgang; Abel, Bernd; Naydenov, Boris; Jelezko, Fedor
Abstract: Here we report the synthesis of 13 C-enriched diamond powder with sub-micron particle sizes via High Pressure High Temperature (HPHT) growth. Diamond powder with a tailored isotopic enrichment is particularly interesting for implementation of Dynamic Nuclear spin Polarization (DNP) and 13 C enrichment plays an important role for increasing the signal to noise ratio in Nuclear Magnetic Resonance (NMR) and Magnetic Resonance Imaging. We applied Electron Paramagnetic Resonance (EPR) and NMR spectroscopy to the sub-micron diamond material as well as Optically Detected Magnetic Resonance (ODMR) and atomic force microscopy to investigate preselected nano-sized particles. The 13 C spin concentrations were evaluated with NMR for the initial particle ensemble and with ODMR for the nanodiamond fraction, showing the homogeneous distribution of 13 C density in particles with different sizes. The 13 C nuclear spin-lattice relaxation decay ( T 1 ) shows a multiexponential behavior, where the fast relaxing component is attributed to relaxation from surface defects. Additionally, an optical method for estimating the NV − concentration in nanodiamonds is presented. The obtained powder is promising as a base material for the production of 13 C-enriched nanodiamonds for DNP applications. Graphical abstract: Image 1